Examining the concept of Unity of Existence according to the perspective of Islamic philosophers and Mystics - Redi Irawan; Agiel Laksamana Putra; Hisam Sidqi (Yayasan Sinergi Kawula Muda, 2025)
This article discusses the concept of Wahdat Al-Wujud (Unity of Existence) from the perspectives of Islamic philosophers, categorized into three major groups: the Peripatetic philosophy, the Illumination philosophy, and the Transcendental philosophy. Additionally, this article will explore the thoughts of Sufis such as Sheikh Muhyiddin Ibn Arabi and Hamzah Fansuri (Indonesian Archipelago), through several of their works like Asrar Arifin, Sharab al-Ashiqin, and Al-Muntahi. To analyze this discussion, authors employs an analytical-descriptive method, ultimately concluding that among philosophers, the concept of existence (Wujud) is not only self-evident but is also deemed impossible to define. The Peripatetic school believes in Asalatul Wujud, while the Illumination philosophy upholds Asalatul Mahiyah. Interestingly, Mulla Sadra builds the foundation of his philosophy on the concept of Asalatul Wujud. Yet, he can explain the theory of Taskik Wujud through the metaphor of light, which has often been discussed in Illumination philosophy. The concept of Unity of Existence in mysticism asserts that there is only one true existence: the existence of the Divine Essence, and all that exists are manifestations. It does not deny multiplicity (Kasrat); however, it is found in the appearances and manifestations, not in existence itself.